Testy warunków skrajnych jako element oceny bezpieczeństwa sektora bankowego - Mikołajczyk, Marcin (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article presents the latest approach to stress tests applied by the EuropeanBanking Authority and national supervisory authorities, including methodology,scenarios, key assumptions and results of a study. The results of stress testsindicate that the banking sector in Poland is in good condition as banks showedhigher level of capital adequacy than most of the banks from the European Union,reflecting the stability of the banking sector. Stress test methodology used by theEuropean Central Bank is also contained in the paper. The role of stress tests asan instrument for enhancing the stability of financial institutions and the needfor further work on stress testing are also discussed.